Bit by bit : an iconographic study of horses in the reliefs of the Assyrian king Ashurnasirpal II (883 - 859 BC) - Baldwin, Stephanie (Stellenbosch : Stellenbosch University, 2014)
Thesis (MPhil)--Stellenbosch University, 2014.